2022
DOI: 10.1177/0958305x211073800
|View full text |Cite
|
Sign up to set email alerts
|

Changing the regulations for regulating the changes: From distribution system operator (DSO) to electricity distribution stakeholders’ organization (EDSO)

Abstract: Followed by the extensive activation of demand side entities, the anti-competitive and monopolistic aspects of distribution system operator (DSO) is becoming more apparent. The business model of the DSO and its regulations are not capable enough to fully leverage the capacity of emerging technologies and responsive prosumers. This paper criticized the challenges/deficits revolving around the conventional DSO model and proposes an interactive platform based on the sharing economy business model at the network l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Electricity generation [1], [2], transmission [3], [4], and distribution [5], [6] to users are the responsibility of utility companies a major aspect of this responsibility is the provision of a safe yet dependable power supply to the users [7]. Utility companies all over the world have complex protective devices installed on their power system equipment for the safety and protection of the transmission and distribution networks from problems.…”
Section: Introductionmentioning
confidence: 99%
“…Electricity generation [1], [2], transmission [3], [4], and distribution [5], [6] to users are the responsibility of utility companies a major aspect of this responsibility is the provision of a safe yet dependable power supply to the users [7]. Utility companies all over the world have complex protective devices installed on their power system equipment for the safety and protection of the transmission and distribution networks from problems.…”
Section: Introductionmentioning
confidence: 99%
“…A common feature of all these suggested models is the provisioning of a local electricity market at ADN level. Solat et al [10] investigated the challenges surrounding these operation models in the presence of high-penetrated ACs and concluded that their associated DSO business model, although more active, is still monopolistic and for-profit. Some of these challenges are:…”
Section: Introductionmentioning
confidence: 99%
“…As can be concluded, restructuring of ADN operation model takes precedence over the formation of electricity market at ADN level. Solat et al [10] have proposed the electric distribution stakeholder organization (EDSO) as a non-profit and non-monopolistic entity for ADN operation and planning. The business model of the EDSO were proposed in [10]; however, technical investigation of planning and operation of ADNs under the management of EDSO has yet to be addressed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation